Bioethanol production from paperboard mill sludge using acid-catalyzed bio-derived choline acetate ionic liquid pretreatment followed by fermentation process. (1st August 2017) - Farghaly, Ahmed; Elsamadony, Mohamed; Ookawara, Shinichi; Tawfik, Ahmed
Graphical abstract: Highlights: Total reducing sugar concentration depends on [ChO][OAc] ionic liquid to biomass ratio. Acid-catalyzed ionic liquid significantly enhance pretreatment process. Prolonged pretreatment duration degraded sugars into furans compounds. Maximum net energy of 5.36 ± 0.30 kJ/gPMS obtained by using acid catalyst IL. Abstract: Paperboard mill sludge (PMS) composed of cellulose, hemicellulose, lignin and ash contents of 36.72 ± 2.81, 32.91 ± 1.75, 22.89 ± 0.56, and 7.48 ± 0.39%, respectively. Enzymatic hydrolysis process followed by fermentation of native PMS provided an ethanol yield of 0.36 ± 0.01 g/L which equivalent to net gain energy of −0.84 ± 0.03 kJ/gPMS . Choline acetate ionic liquid [Cho][OAc] IL was extensively used as a solvent for PMS to upgrade the performance. Pretreatment with [Cho][OAc] IL/PMS ratio of 10% (w/w) for 1.0 h, at a temperature of 120 °C exhibited hemicellulose and lignin removal efficiency of 5.05 ± 0.52 and 14.71 ± 1.22%, respectively with 89.19 ± 5.62% cellulose recovery. This corresponded to net gain energy of 0.60 ± 0.04 kJ/gPMS based on ethanol yield from enzymatic saccharification process which was quite low due to a limited hemicellulose removal and glucose yield of 24.1 ± 1.4 g/L. [Cho][OAc] IL/PMS ratio of 10% (w/w) supplemented with 1% (v/v) HCl substantially improved the removal efficiency of hemicellulose (36.38 ± 4.51%), lignin (17.42 ± 1.19%) and cellulose (82.17 ± 4.28%) which provided the maximum net energy of 5.36 ± 0.30 kJ/gPMS .